2017
DOI: 10.1017/bca.2017.17
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of U.S. Federal Environmental Regulation

Abstract: Retrospective, or ex post, analysis of U.S. federal regulation aims to rigorously document regulatory outcomes using cost, benefit, and distributional metrics. This paper presents nine new case studies involving a total of 34 comparisons of ex ante and ex post estimates from a diverse group of environmentally oriented rules. Despite the potential for selection bias and other limitations of the case study approach, the results suggest a slight tendency to overestimate both costs and benefits (or effectiveness) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…This is in stark contrast to the literature on retrospective analysis of the cost of environmental regulations in the United States, where it is found that ex ante costs were overestimated or unbiased(Kopits et al, 2014;Wolverton, 2014;Morgenstern, 2017).…”
contrasting
confidence: 98%
“…This is in stark contrast to the literature on retrospective analysis of the cost of environmental regulations in the United States, where it is found that ex ante costs were overestimated or unbiased(Kopits et al, 2014;Wolverton, 2014;Morgenstern, 2017).…”
contrasting
confidence: 98%
“…One defining feature of the research on the costs of the Clean Air Act is that predicted costs of the regulations are often higher than the costs that actually occur. Morgenstern (2018) provides an overview of the ways in which prospective and retrospective analyses have differed for nine separate environmental policies. There are at least four reasons why this pattern may arise.…”
Section: Predicted Versus Actual Costs Of the Clean Air Actmentioning
confidence: 99%
“…Evaluating the effectiveness of such treaties and policies is difficult because deriving causal inferences and accurate attribution requires accounting for several confounding factors, and direct and indirect spillovers (Isaksen 2020). Nevertheless, several studies assess the effectiveness of such treaties and regulations (De Foy et al 2016;Li et al 2017aLi et al , 2017bMorgenstern 2018;Mardones and Cornejo 2020). However, there is little ex-post empirical analysis and a greater focus on ex-ante studies in the literature.…”
Section: Emission Impacts Of Other Related Policiesmentioning
confidence: 99%